Identitas Bayangan Konsep Limas:Analisis Terhadap Konsepsi Matematis Siswa - Tri Rahayu; Fiki Alghadari (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
This study aims to analyze the identity of the shadow of the pyramid concept based on the students' mathematical conception. This study was conducted by surveying participants through a question. Survey questions contain two concept definitions, namely the length of all ribs equal to 4 cm, and have diagonal sides. The participants were students of class XII-IPA in one of the Belitung District High School in the academic year 2018/2019. The answer to the survey question was the students' conception of the concept for the shape of the pyramid building. Analysis of student conceptions focused on identification points, such as ribs, shapes, side diagonals, base fields and pyramid erect sides. From the data analysis, four kinds of student shadow concept identities were obtained. Level geometry thinking students who stated that not all pythons were the same. length is at the level of analysis. While students who state the pyramid side do not have diagonals indicate their level of thinking is at the level of visualization. While students at the level of thinking abstraction are characterized by the identity of the yaitulimas concept having diagonal sides, irregular rectangular pyramid with diagonal sides on the base to identify the relationship between the diagonal side, pyramid height, and elements of the pyramid forming field.